CHALLENGES AND SOLUTIONS TO INCREASE YOUTH PARTICIPATION IN RELIGIOUS ACTIVITIES - S. Adam, Muh. Wahyuddin; Abdulrahman, Anisa; Nawawi, Natasya; Hulopi, Friskilan; Djingo, Sri Meliyanti; Kurniawati, Astrid (Academic Solution Publisher, 2024)
In modern usage, the word